Evaluation of the Rationality of Antibiotic Use in Child Diarrhea Patients in the Inpatient Care Installation - Truly Anggraini; Retnowati Adiningsih; Khoirun Nisa Logarithm (GLOBAL HEALTH SCIENCE GROUP, 2025)
According to WHO and UNICEF, diarrheal disease occurs around 2 million cases and 1.9 million children die each year with a prevalence of 78% in developing countries. The treatment used is antibiotics. Irrational use of antibiotics can cause less effective treatment, decreased drug safety levels, high treatment costs and increased resistance. The purpose of this study was to evaluate the rationality of antibiotic use in pediatric diarrhea patients at UNS Hospital using the Gyssens method for the period January - September 2023. This study was conducted as an observational study with a descriptive design with retrospective sampling, the sample of this study was 80 patients and included in the inclusion category of 33 samples, then a descriptive analysis was carried out using the Gyssens assessment. The reference used is the Indian guidelines Academy of Pediatrics (IAP) 2022, DIH, MIMS, and UNS Hospital Drug Formulary. Data collection began with observation of medical records of pediatric diarrhea patients at UNS Hospital. The research data was obtained from UNS Hospital medical records for the period January - September 2023, then analyzed using the Gyssens method which was categorized as 0 - 6 descriptively and presented in the form of a percentage.This study shows the results of the rationality of antibiotics for pediatric diarrhea patients in the inpatient department of UNS Hospital using the Gyssens method for the period January - September 2023 proving that 71.73% of patients received rational antibiotic therapy (category 0), as many as 28.27% of patients received irrational antibiotic therapy including 10.87% category IVC, namely there are cheaper alternatives, 6.53% category IIIB, namely the duration of antibiotic use is too short, 10.87% category IIB, namely the interval of antibiotic administration is not appropriate.